Respuesta :
Multiplying -3 and 4 to get -12
The first step is multiplying -3 and 4 because they are all in parentheses and using PEMDAS
P-Parentheses
E-exponents
M-multiply or D- division (whichever is first in the expression)
A-addition or S-subtraction (whichever is first in the expression)
Answer: you multiply because of pendants
Step-by-step explanation:
P = parentheses
E = exponent
M = multiplication
D = division
A = addition
S = subtraction
Always follow the pemdas when it comes to an equation like that
Take a screenshot just to have it in mind